Effects on Firm Decisions Considering the Temporality of Environmental Policy - Zamorano-Ford, J (Inderscience Publishers, 2025)
This research analyses the effects of the temporality of environmental policy on firms’ location and abatement decisions. The policies are implemented by a regulator concerned about the welfare of society and environmental pollution. Therefore, it applies two instruments simultaneously: the tax on emissions, which seeks to internalise environmental costs, and the subsidy to clean technologies, which incentivises their adoption. In addition, the optimal levels of tax and subsidy that maximise social welfare are studied, considering the impact of the timing of the decision (ex-ante or ex-post). As for its resolution, a model of duopolistic firms competing in quantities in an emission-intensive sector is used. Among the main results, it is demonstrated that for both an ex-ante and ex-post implementation, social welfare is enhanced when environmental policies are in place. However, when the tax is applied ex-post and only one company chooses to remain in the local country, environmental damage increases. © 2025 Inderscience Enterprises Ltd.
Keywords: emission tax; environmental regulation; location; subsidy R&D; temporality of the decision